Evaluation of early musculoskeletal disease in patients with haemophilia: results from an expert consensus. Issue 6 (September 2018) - Seuser, Axel; Djambas Khayat, Claudia; Negrier, Claude; Sabbour, Adly; Heijnen, Lily
Abstract : N/A: Early joint damage in patients with haemarthrosis often escapes diagnosis because of insufficient investigation of biomechanical changes. Arthropathy in haemophilia requires complex assessment with several tools. Considering the increased emphasis on an integrated approach to musculoskeletal (MSK) outcomes, re-evaluation of MSK assessment to address individual patient needs is warranted. To advise on the optimal use of current assessment tools and strategies for tailored MSK evaluation in patients with haemophilia. A panel of experts in haemophilic arthropathy evaluated internationally recognized assessment tools through published literature and personal expertise. Each tool was considered, scored and ranked for their utility in the clinical assessment of MSK damage. Subsequently, a patient evaluation table detailing advice on type and frequency of assessments for different patient populations was constructed. To obtain a complete MSK assessment, multiple tools must be used to ensure each criterion is evaluated. For patients with haemophilia, clinical examination of the joint, disease-specific structure/function scores, and activity/participation scores including quality of life are important, and should be performed on a regular basis according to age and clinical condition. Joint imaging is recommended in the prevention, diagnosis and follow-up of haemophilic arthropathy and should be used in conjunction with joint structure and function scores. An integrated approach to MSK assessment using combinations of tools will allow earlier management of dysfunction and may improve long-term outcomes. This approach could be used in long-term follow-up of all patients independent of age and disease stage, especially in children to prevent arthropathy.